Crinkleroot's guide to knowing the trees - Arnosky, Jim (Bradbury Press, 1992)
An illustrated introduction to trees and woodlands with information on how to identify the bark and the leaves, the many ways that animals use trees, and how to read the individual history that shapes every tree.